A NEW SPECIES OF FORSTERINARIA GRAY, 1973 (LEPIDOPTERA: NYMPHALIDAE: SATYRINAE) FROM THE SERRANÍA DEL PERIJÁ, CESAR, COLOMBIA - PULIDO-B. HANNIER W.; ANDRADE-C. M. GONZALO (Caldasia)
A new species of butterfly from the Serranía del Perijá, Cesar, Colombia, is described herein. A mountain system where the principal characteristic of the high altitude lands is the biogeographic isolation from other Andean mountain systems such as the Sierra Nevada de Santa Marta and the Sierra de Mérida in Venezuela. This new species is close to Forsterinaria punctata, but shows clear differences in the wing pattern coloration and the male genitalia morphology